DOI: 10.29007/2qv6
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of Alternative Splicing in Soybean Plants

Abstract: Alternative splicing (AS) increases the diversities of transcriptomes and proteomes in plants. The work reports identification and analysis of genes and their transcripts with a focus on AS in soybean plants by integrating mapping information of over 1.5 million of mRNAs and expressed sequence tags (ESTs) with more than 6 billons of mapped reads collected from 90 RNA-seq datasets obtained from multiple experiments. A total of 294,164 AS events were detected and categorized into basic events (151,710, 51.57%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…TE insertion is probably an important mechanism for IR-type AS in maize. The AS levels of 3864 genes were significantly different between maize and teosinte, of which 151 AS levelaltered genes involved in transcriptional regulation and in stress responses were located in the regions that were targets of selection during maize genetic improvement [177].…”
Section: Grain and Fiber Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…TE insertion is probably an important mechanism for IR-type AS in maize. The AS levels of 3864 genes were significantly different between maize and teosinte, of which 151 AS levelaltered genes involved in transcriptional regulation and in stress responses were located in the regions that were targets of selection during maize genetic improvement [177].…”
Section: Grain and Fiber Cropsmentioning
confidence: 99%
“…Over 11,000 novel splice isoforms, alternative polyadenylation (APA) of ~11,000 expressed genes and more than 2100 novel genes were reported in sorghum [30,178], whereas 15,102 fiber-specific AS were reported in cotton [99]. To date, a large number of AS events associated with various development stages and molecular functions have been reported in soybean-294,164 AS events across multiple experiments [177]; 1278 AS events associated with nitrate stress in root hairs [179]; and 154,469 AS events in 23,764 genes across development stages [180]. The intron retention form of AS events was predominant in most of the research reported here followed by alternative acceptor sites, alternative donor sites, and exon skipping.…”
Section: Grain and Fiber Cropsmentioning
confidence: 99%